Occurrence of cystoisosporosis among domestic cats in Thrissur district, Kerala - E. S. Neeraja; P. V. Tresamol; K. Vijayakumar; V. H Shyma; K. Syamala (Journal of Veterinary and Animal Sciences, 2023)
This study was aimed to evaluate the prevalence of cystoisosporosis among domestic cats in Thrissur district, Kerala. A total of 155 cats were included in this study. Faecal samples collected from all the cats were subjected examination by direct smear method and floatation by Sheather’s sugar solution. Of 155 faecal samples examined, oocysts were found in 28 cats (18.06 per cent). Among these, 12 were collected from cats with signs of gastrointestinal diseases and 16 from cats which are apparently healthy with firm faeces. Mixed infection with Cystoisospora spp and Toxocara, Ancylostoma and Cystoisospora were also detected in three (1.94 per cent) and one (0.65 per cent) cat respectively. Various risk factors associated with the infection were also studied. Prevalence was found to be higher in cats less than six months old. Gender and breed were not affected the prevalence. This study demonstrates that cystoisosporosis is common in cats.